PERTUMBUHAN EKONOMI DAN KUNJUNGAN WISATAWAN DALAM PARADIGMA PERSPEKTIF ISLAM - Syafa'at, Ahmad Munib; Jauhariyah, Nur Anim; Mahmudah (Jurnal Istiqro, 2025)
This study aims to describe the relationship between economic growth and tourist arrivals and to examine their interconnection from an Islamic perspective. Time-series data indicate that the development of the tourism sector in Banyuwangi Regency contributes to the dynamics of regional economic growth. Prior to the pandemic, both economic growth and tourist arrivals showed positive trends, whereas during the pandemic, both experienced a sharp decline and subsequently increased again during the recovery period. These findings align with the tourism-led growth theory, which posits that tourism serves as one of the main drivers of economic activity through income generation and job creation. From an Islamic perspective, economic activities and tourism development must be oriented toward maslahah, justice, and sustainability, and carried out in a halal, ethical manner that avoids harm. The results of this study demonstrate that strengthening the tourism sector can serve as a development instrument compatible with the principles of maq??id al-syar?’ah, implying that economic growth should be assessed not only in material terms but also in terms of broader social welfare and public benefit. Thus, the integration of economic growth, increased tourist arrivals, and Islamic values provides a conceptual foundation for sustainable and equitable tourism development